A middle aged man with Caroli's disease: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Caroli's disease (CD) is a rare congenital abnormality characterized by non-obstructive dilatation of intra hepatic bile ducts, which may be complicated by stone formation, recurrent cholangitis, biliary abscess and higher risk for biliary malignancy. We report a 37-year-old man with recurrent bouts of upper abdominal pain, high grade pyrexia, mild icterus with normal liver function tests who was diagnosed as a case of Caroli's disease. The laboratory studies confirmed Caroli' s disease with a SOL in liver suggestive of liver abscess and the patient received broad spectrum antibiotics with anaerobic and amoebicidal coverage. With 14 days course of antibiotics, he gradually recovered from his symptoms.